2021
DOI: 10.1109/access.2021.3072435
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Agent Reinforcement Learning-Based Resource Management for End-to-End Network Slicing

Abstract: To meet the explosive growth of mobile traffic, the 5G network is designed to be flexible and support multi-access edge computing (MEC), thereby improving the end-to-end quality of service (QoS). In particular, 5G network slicing, which allows a physical infrastructure to split into multiple logical networks, keeps the balance of network resource allocation among different service types with on-demand resource requests. However, achieving effective resource allocation across the end-to-end network is difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Consequently, RL is becoming a standard approach for resource management in network slicing. The main issues addressed by RL in this domain have been: resource management for virtualized functions [9], [11], [23]- [26], admission control of new slices [9], [15], [16], handling of computational resources in mobile edge computing (MEC) [11], [27], [28], UE scheduling [29], [30], and radio resource allocation among network slices [13], [18], [19], [31], [32], which is the problem addressed in this work.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, RL is becoming a standard approach for resource management in network slicing. The main issues addressed by RL in this domain have been: resource management for virtualized functions [9], [11], [23]- [26], admission control of new slices [9], [15], [16], handling of computational resources in mobile edge computing (MEC) [11], [27], [28], UE scheduling [29], [30], and radio resource allocation among network slices [13], [18], [19], [31], [32], which is the problem addressed in this work.…”
Section: Related Workmentioning
confidence: 99%
“…In the last few years, RL and DRL techniques have increasingly attracted research community interest, due to their robustness and dynamicity. They have demonstrated them superlatively in the context of dynamic channel allocation, and many papers [47][48][49][50][51][52][53][54][55] have mainly based on the Q-learning, SARSA, expected SARSA, Monte Carlo, and Actor-Critic (A2C), to allocate radio or edge/fog resources to network slices, in order to maximise the operator revenue, QoS satisfaction, and resource utilisation. To deal with scalability issues faced by RL-based approaches, the approaches in Ref.…”
Section: Elhachmi -209mentioning
confidence: 99%
“…Related studies can be found in the following sources but not restricted to Ref. [7–87]. Each of the proposed techniques has its own advantages and disadvantages, and none of them can be considered on its own to fully accomplish the realisation of CR systems.…”
Section: Introductionmentioning
confidence: 99%
“…maximize resource utilization while ensuring an acceptable level of performance). More specifically, the existing proposals focused on tracking and optimizing a single metric like coverage [6], power management [7], throughput [8] and resource sharing [9] at a time. It flows directly from this limited focus that current approaches resort to often applying a single control action, e.g.…”
Section: Introductionmentioning
confidence: 99%